2012
DOI: 10.1038/nature10970
|View full text |Cite
|
Sign up to set email alerts
|

Layered boron nitride as a release layer for mechanical transfer of GaN-based devices

Abstract: Nitride semiconductors are the materials of choice for a variety of device applications, notably optoelectronics and high-frequency/high-power electronics. One important practical goal is to realize such devices on large, flexible and affordable substrates, on which direct growth of nitride semiconductors of sufficient quality is problematic. Several techniques--such as laser lift-off--have been investigated to enable the transfer of nitride devices from one substrate to another, but existing methods still hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
289
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(309 citation statements)
references
References 28 publications
6
289
0
Order By: Relevance
“…[ 5 ] There have also been efforts and demonstrations in separating µm-thick GaN device structures from substrates using laser liftoff, [ 6 ] chemical liftoff, [ 7 ] electrochemical liftoff, [ 8,9 ] and mechanical liftoff on suitable buffer layers. [ 10,11 ] These works open the way for vertical device confi guration but fall short in the pursuit of ultrathin (<500 nm), mechanically fl exural membranes. As the freestanding layer thickness decreases to below 500 or even 100 nm, the fl exural rigidity of the layer is expected to decrease dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] There have also been efforts and demonstrations in separating µm-thick GaN device structures from substrates using laser liftoff, [ 6 ] chemical liftoff, [ 7 ] electrochemical liftoff, [ 8,9 ] and mechanical liftoff on suitable buffer layers. [ 10,11 ] These works open the way for vertical device confi guration but fall short in the pursuit of ultrathin (<500 nm), mechanically fl exural membranes. As the freestanding layer thickness decreases to below 500 or even 100 nm, the fl exural rigidity of the layer is expected to decrease dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…Kobayashi et al, demonstrated MOCVD-grown h-BN as a releasing layer for transferring the GaN-based LED epitaxial structure grown on the h-BN onto foreign flexible substrates. [15][16][17] Recently, Q. S. Paduano et al, reported self-terminating effect in MOCVD growth of h-BN 18 and investigated effects of growth parameters including reactor pressure, and V/III ratio, defined as molar flow ratio between NH 3 and triethylborane (TEB) which are source of nitrogen and boron respectively, on thickness of MOCVD-grown h-BN. 19 X.…”
mentioning
confidence: 99%
“…With an energy bandgap around 6.5 eV, h-BN is emerging as an important semiconductor material. [3][4][5][6][7] With its unique physical properties including high temperature and chemical stability, h-BN has potential applications in high temperature/power electronic device applications. P-type conductivity seems to be more easy to realize in h-BN than in AlN, which reveals the potential of h-BN for deep UV emitter and detector applications.…”
mentioning
confidence: 99%